2016
DOI: 10.1039/c6nr03490j
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering of nanoporous anodic alumina optical bandpass filters

Abstract: Herein, we present a rationally designed advanced nanofabrication approach aiming at producing a new type of optical bandpass filters based on nanoporous anodic alumina photonic crystals. The photonic stop band of nanoporous anodic alumina (NAA) is engineered in depth by means of a pseudo-stepwise pulse anodisation (PSPA) approach consisting in pseudostepwise asymmetric current density pulses. This nanofabrication method makes it possible to tune the transmission bands of NAA at specific wavelengths and bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…This top-down nanofabrication approach offers industrial scalability (from mm 2 to m 2 ), cost-competitiveness, and versatile control over the features of nanopores, which can be modulated with precision by means of the anodization parameters to generate unique multi-dimensional PC structures able to guide, reflect, modulate, confine, transmit, emit, and enhance incident light selectively across the spectral regions 17 , 18 . Recent studies have demonstrated that rationally designed pulse-like anodization profiles under suitable conditions enable the precise engineering of the photonic stopband (PSB) of NAA-PCs by creating structures such as gradient index filters 19 22 , optical microcavities 23 , distributed Bragg reflectors 24 – 28 , bandpass and linear variable bandpass filters 29 , 30 . These PCs can be used as optical filters for a plethora of applications due to the flexibility and selectively to engineer their light-filtering features across the spectral regions 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…This top-down nanofabrication approach offers industrial scalability (from mm 2 to m 2 ), cost-competitiveness, and versatile control over the features of nanopores, which can be modulated with precision by means of the anodization parameters to generate unique multi-dimensional PC structures able to guide, reflect, modulate, confine, transmit, emit, and enhance incident light selectively across the spectral regions 17 , 18 . Recent studies have demonstrated that rationally designed pulse-like anodization profiles under suitable conditions enable the precise engineering of the photonic stopband (PSB) of NAA-PCs by creating structures such as gradient index filters 19 22 , optical microcavities 23 , distributed Bragg reflectors 24 – 28 , bandpass and linear variable bandpass filters 29 , 30 . These PCs can be used as optical filters for a plethora of applications due to the flexibility and selectively to engineer their light-filtering features across the spectral regions 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The optical spectrum of these NAA-PCs has a characteristic PSB when light flows transversally through the NAA-FPIs’ structure, which is established by the interpore distance (i.e., lattice constant) and porosity (i.e., nanopore diameter) [ 46 , 47 , 48 , 49 ]. NAA-BPFs are PC structures that allow the transmission of a specific portion of the light spectrum in a selective manner while impeding the pass of light of all other wavelengths [ 79 , 86 ]. NAA-BPFs can be classified into three categories according to the range of allowed wavelengths: (i) longpass filters, which allow the transmission of light of long wavelengths, (ii) shortpass filters, which allow the pass of light of short wavelengths, and (iii) bandpass filters, which allow the transmission of a band of wavelengths while blocking the pass of light of shorter and longer wavelengths.…”
Section: Fabrication and Properties: Nanoporous Anodic Alumina As mentioning
confidence: 99%
“…As demonstrated in previous studies, this blue shift is associated with the reduction of the anodization period, which results in a shorter period length (L TP ) within the nanoporous structure of NAA-µCVs. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The transmission spectra of these NAA-µCVs displays a PSB that increases its intensity with t pw and a well-defined resonance band at the center of the PSB. The quality factor (Q C ), defined as the ratio of the resonance band wavelength (λ R ) to its full width at half maximum (FWHM R ) (Equation 5), is an important criteria in assessing the strength of photon confinement within optical microcavities.…”
Section: Figure 2bmentioning
confidence: 99%